Deserción universitaria en estudiantes de cuarto y quinto ciclo de la Carrera de Medicina de la Universidad Nacional de Loja - Ordoñez Maldonado, Marjorie Isabel (2024)
Despite the efforts and the different educational policies related to guarantee the permanence of students in the universities, there is evidence of dropout, repetition and abandonment in the first levels of the careers, For this reason, the present research was developed with the objective of determining the predisposing factors for university desertion in fourth and fifth cycle students of the medical career of the National University of Loja during the academic period October 2022 - March 2023, developing a quantitative, descriptive, cross-sectional study in which 103 students participated who were administered the University Student Dropout Survey (EDEU) and the Academic Experiences Questionnaire – short version (QVA-r). The results show that 63.11% were aged 18-20 years, 99.03% were of mixed race, 97.09% were single, 72.82% were female, 3.88% had children, 8.74% worked in addition to studying, 27.18% lived alone, 7.77% lived with other family members and only 2.91% lived with their partner; 19.42% of the students' households earn less than a basic salary, 7.77% finance their studies personally, 14.56% suffer from illnesses that require medical follow-up, and the majority come from provinces belonging to zone 7. Among the causes for dropping out, socioeconomic factors were identified, related to the student's personality, academic and cultural factors, reasons for the university to evaluate the services provided by the university welfare department and guarantee the student's educational process so that it is not interrupted due to lack of economic resources or situations related to mental health